An exploration of communication strategies influencing public responses to climate change - Beard, Caroline, author; Thompson, Jessica, advisor; Vaske, Jerry, committee member; Sprain, Leah, committee member (Colorado State University. Libraries, 2012)
This thesis is an exploration of communication strategies and U.S. public responses to climate change. The exploration begins with an in-depth case study based in Southern Florida and proceeds with a focused analysis of U.S. National Park and U.S. National Wildlife Refuge visitors and their concern and responsibility for climate change, as well as their engagement with energy-conserving actions. Through the lens of place-based climate change communication, the third chapter of this thesis compares results from internal and external assessments of capacity to communicate about climate change at national parks and wildlife refuges in southern Florida. The internal survey sample included agency staff, stakeholders, community partners and concessionaires; the external survey sample included visitors to Everglades and Biscayne National Parks and Ten Thousand Islands and the National Key Deer Refuges. Results demonstrate a significant gap in visitors' versus staff and partners' awareness of climate change impacts in these areas. Communicating with the public about climate change is not currently a top priority for the region's protected areas and partners, but the opportunity to engage visitors in this issue through place-based education is supported with this study. The second component of this exploration examines the relationships between political affiliation, ascription of responsibility (AR), beliefs about climate change causes, salience, and reported pro-environmental behaviors to test the following hypotheses: [H1] climate change salience is higher for Democrats than Republicans; [H2] as AR increases, climate change becomes more salient; [H3] for respondents who believe human actions contribute to climate change, salience is higher; [H4] as salience increases, the number of respondents' reported energy-conserving behaviors increases; [H5] respondents who believe humans are causing climate change report engaging in more energy-conserving behaviors; [H6] AR increases as the number of visitors' reported pro-environmental behaviors increases. Using an on-site sampling method, we administered 4,181 surveys to national park and wildlife refuge visitors in 16 sites across the United States. Results of regression analyses confirmed H1 through H6, and additional significant relationships were found in the path model. These findings indicate that strategic communication could potentially enhance public engagement in climate change mitigation and energy-conserving actions.
Keywords: climate change; wildlife refuge; public communication; place-based education; national park